Analysis of Scale Deposit in the Geothermal Power Plant - Afifah Harmayanti; Suwarno Suwarno (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2018)
Gunung Salak is one of the potential geothermal area in Indonesia. The steam character is categorised as the water – dominated steam with low steam purity. During inspection, deposit was found in several equipment which are turbine, demister, scrubber and separator. Demister is an essential in the geothermal system as it keeps the steam quality above the saturated condition, by removing the water phase from the steam. The deposit was predicted to be form because of scaling problem due to the impurities of the steam. Oxygen is expected to be responsible of the scaling problem. This research is to analyze the effect of oxygen partial pressure to the formation of scaling through thermodynamic approach. The formation of iron oxide scaling is to be focused in this research as it is mostly found in the deposit alongside other compounds. Demister’s deposit was analyzed using ICP, AAS, XRD and SEM – EDX method. The actual composition found in the demister is then compared to the phase stability diagram results using a chemical reaction software. The deposit used is from the demister.